Synthesis of Cobalt Nanowires on Porous Anodic Alumina Template Using Electrochemical Deposition - Chung, C.K.; Wu, S.H.; Hsu, C.R.; Tsai, C.H.; Chung, I.C. (Journal of Coating Science and Technology, 2016)
Electrochemical deposition has been widely used for synthesis of metal nanowires (NWs) on the porous template. In this paper, the effect of potential and electrolyte concentration on cobalt (Co) NWs formation through porous anodic alumina template has been investigated using direct-current electrodepostion at 0.75~2 V together with the high 0.5 M and low 0.1 M cobalt sulfurate based electrolyte. Scanning electron microscopy and grazing incidence X-ray diffraction were used to examine the nanostructure, morphology and phase of Co NWs. The current vs time curve was recorded for understanding the growth behavior. Too low potential of 0.75 V is not favored for Co NWs formation due to insufficient driving force while too high potential of 2 V ruins the NWs growth owing to hydrogen generation in reduction reaction. The uniform crystalline Co NWs can be obtained by the proper potential of 1V and concentration of 0.5 M at an average growth rate of 964 nm/min.